2005
DOI: 10.1093/rheumatology/kei192
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic postural balance in ankylosing spondylitis patients

Abstract: AS has no negative effect on postural stability. The only clinically significant association was found between dynamic postural balance and TWD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
70
0
4

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(75 citation statements)
references
References 13 publications
1
70
0
4
Order By: Relevance
“…Previously, only static or dynamic balance were assessed in AS patients. [5][6][7] However, we were unable to detect any trial in the literature assessing both static and dynamic balance in AS patients. Therefore, factors affecting balance in AS patients are still unclear.…”
mentioning
confidence: 82%
See 1 more Smart Citation
“…Previously, only static or dynamic balance were assessed in AS patients. [5][6][7] However, we were unable to detect any trial in the literature assessing both static and dynamic balance in AS patients. Therefore, factors affecting balance in AS patients are still unclear.…”
mentioning
confidence: 82%
“…2 It has been shown that AS patients required more energy to control their COG. [3][4][5] Impaired control of COG results in balance disorders and falls. Falls were reported as the leading cause of spinal fractures.…”
mentioning
confidence: 99%
“…In the results of the study, a positive relationship was only found between the tragus-wall distance and the mediolateral stability index. No other relationship was determined between the BASMI score of other stability indexes and disease duration and it was therefore reported that there was a high probability of dynamic balance loss in AS [14].…”
Section: Literature Reviewmentioning
confidence: 99%
“…In the first study in literature examining the relationship of AS and postural balance, Murray et al showed a higher rate of impaired balance in AS patients compared to healthy individuals [13]. However, in a later study, no impairment could be shown in the postural stability of AS patients [14].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation